Use of Combined Microautoradiography and Fluorescence In Situ Hybridization To Determine Carbon Metabolism in Mixed Natural Communities of Uncultured Bacteria from the Genus Achromatium - Gray, N. D. (American Society for Microbiology, 2000)
Combined microautoradiography and fluorescence in situ hybridization (FISH) was used to investigate carbon metabolism in uncultured bacteria from the genus Achromatium. All of the Achromatium species identified in a freshwater sediment from Rydal Water, Cumbria, United Kingdom, which were distinguishable only by FISH, assimilated both [(14)C]bicarbonate and [(14)C]acetate. This extends previous findings that Achromatium spp. present at another location could only utilize organic carbon sources. Achromatium spp., therefore, probably exhibit a range of physiologies, i.e., facultative chemolithoautotrophy, mixotrophy, and chemoorganoheterotrophy, similar to other large sulfur bacteria (e.g., Beggiatoa spp.).